Impact of water deficit (salt and drought) stress on physiological, biochemical and yield attributes on wheat (Triticum aestivum) varieties - KUMAR, ASHWANI; SHARMA, SURINDER KUMAR; LATA, CHARU; DEVI, RITU; KULSHRESTHA, NEERAJ; KRISHNAMURTHY, S L; SINGH, KAILASH; YADAV, RAJENDER KUMAR (The Indian Journal of Agricultural Sciences, 2018)
This investigation was carried out to assess the combined effect of salt stress and drought on physiological and biochemical traits in wheat (Triticum aestivum L.) varieties so as to deduce the probable mechanism of stress tolerance in these varieties. Two salt tolerant (Kharchia 65 and KRL 210) and two salt sensitive (HD 2851 and HD 2009) wheat varieties were subjected to salt (50 mM and 100 mM NaCl) and drought (25% and 50% water deficit) stresses alone as well as in combination to study the interactive effects of salt × drought stresses under pot house conditions at seedling stage. The data recorded on physiological (membrane injury, relative water content, chlorophyll content, Na+, K+, Cl- and K+/Na+), biochemical (total soluble sugars and proline) and yield (number of tillers, productive tillers, biomass, and 1000 seed weight) attributes indicated the effect of salt and drought stresses in the studied varieties. These stresses caused a significant decline in chlorophyll content, K+ content, number of tillers, number of productive tillers, biomass and yield in sensitive varieties, while the tolerant ones were least affected. The sensitive varieties HD 2851 and HD 2009 accumulated the highest Na+ and Cl+ content, whereas Kharchia 65 (tolerant) accumulated the lowest amount of these ions. All the varieties, however, showed increased accumulation of compatible solutes (total soluble sugars and proline) with inclined stress which helped in osmotic adjustment. Consistent and significant reductions were observed in number of tillers as well as in productive tillers with every successive increase in salt and drought stresses. Yield in terms of 1000 seed weight followed the trend: 34.51 g in Kharchia 65>28.52 g in KRL 210>24.89 g in HD 2009>24.55 g in HD 2851.